A sunlit weapon [compact disc, unabridged] : a Maisie Dobbs novel - Winspear, Jacqueline, 1955- (Winspear, Jacqueline, 1955- Maisie Dobbs novel., 2022)
Late September, 1942. Jo Hardy, a 22-year-old ferry pilot, is delivering a Spitfire to Biggin Hill Aerodrome when she realizes someone is shooting at her aircraft. When she returns to the location on foot, she finds an American serviceman in a barn, tied up and gagged. Jo hurries away, but can't shake the image of the serviceman from her mind. Several days later, when Jo recounts the story to several other women, she receives the news that Erica, another ferry pilot, flying the same route she had, has been killed in a crash near Kent. Erica's death is attributed to "pilot error," but Jo is convinced there is a link between her own experience and Erica's, and that of Jo's dead fiancé, who was killed over a year earlier under inexplicable circumstances in the same area. At the suggestion of an Australian colleague, Jo takes her suspicions to Maisie Dobbs, along with two pages of coded notes she found in the barn. If someone is trying to take down much-needed pilots, Maisie wants to find out why, and what happened to the bound American serviceman.